Public Schoolteachers' Attitudes about Religious Liberty in the Classroom. Issue 1 (2nd January 2020) - Olson, Laura R.; Bindewald, Benjamin J.; McCorkle, William D.; Rosenblith, Suzanne N.
Abstract: As agents of the state rather than private individuals while working, U.S. public schoolteachers' 'free exercise rights' are sharply curtailed to prevent them from (dis)favoring any one religion. Are there public schoolteachers who chafe against these constraints, wishing instead for religious accommodations that would grant them the flexibility to refuse to teach required curricular content, or engage in some other form of religious expression or activity in the classroom? If so, who are these teachers, demographically, professionally, religiously, and politically speaking? To answer these questions, we analyze data from an original national email survey of 5, 273 U.S. public schoolteachers.